Pertanggungjawaban Petani yang Melakukan Wanprestasi atas Perjanjian Simpan Pinjam pada KSP Kopdit Pintu Air Cabang Lembor (International Forum of Researchers and Lecturers, 2024)
The purpose of this research is to analyse the liability of farmers who make defaults on savings and loan agreements at KSP Kopdit Pintu Air Lembor branch. The type of research used by the author is Empirical Legal research, the type of data used in this research is qualitative data. The data used in the research based on the relevance of the source data, namely primary and secondary data. The results of this study are that the reasons for the default of farmers on savings and loan agreements at KSP Kopdit Pintu Air Lembor Branch as follows are reduced rice yields and crop failure. The existence of traditional events such as marriage, death and school parties. Income is divided due to financing the education of their children and financing sick families. Farmers borrow from local businesses and communities. Farmers are members of other cooperatives and make loans. Government programmes to improve irrigation have caused farmers not to plant rice. Liability for default by Farmers on savings and loan agreements, namely continuing to pay principal + interest + dues every month and Farmers can repay loans in the form of as much as the member or Farmer can pay or repay the loan and Farmers continue to pay monthly even though only to cover the interest.